Principles of Accounting - Dupree, Dempsey; Marder, Mathew (Massachusetts: Addison-Wesley Publishing, 1984)
This book provides an understandable overview of accounting for non-accounting majors, yet contain sufficient scope and details for accounting majors to acquire a solid foundation for intermediate level courses in accounting.
includes index
jbi, 13/03/2018
Loans
Keywords: accounting